Effects of a Phonological Reading and Writing Remediation Program in Students with Dyslexia: Intervention for Specific Learning Disabilities - Ferraz, Erika; Gonçalves, Thais dos Santos; Freire, Thais; Mattar, Tais de Lima Ferreira; Lamônica, Dionísia Aparecida Cusin; Maximino, Luciana Paula; Abreu Pinheiro Crenitte, Patrícia (Folia phoniatrica et logopaedica, 2018)
Objective: To determine the effects of a phonological remediation reading and writing program in individuals with dyslexia, through behavioral and objective evaluations. Patients and Methods: Twenty children diagnosed with dyslexia, aged 8–14 years, were included in this study. Group I (GI) was composed of 10 children who took part in the program, and group II (GII) consisted of 10 subjects who did not take the remediation. The pre-testing evaluated phonological awareness, rapid naming, working memory, reading and writing of words and nonwords, thematic writing, and auditory evoked potential – P300. The type of stimulus used was the speech (20% of rare stimulus and 80% of frequent stimulus), intensity of 80 dBNa. The rare stimulus was the syllable /da/, and the frequent stimulus was the syllable /ba/. Next, the Phonological Reading and Writing Remediation Program was applied in 24 cumulative sessions, twice a week, each with a duration of 30 min. In the post-testing (at the end of the program), all the tests of the pre-testing were reapplied. Results: There was a statistically significant difference (between pre- and post-testing) in phonological awareness, rapid naming, working memory, thematic writing, writing and reading words and nonwords, as well as in the latency of the P3 component of P300 in GI, while GII maintained the same difficulties. Conclusion: The phonological remediation program showed to be a therapeutic method of fast beneficial effects in written language of individuals with dyslexia. However, the wide age range and the size of the sample could be considered a limitation of this study – it interferes with the generalization of results.